Developing a framework to monitor rural development policy in Ireland: Opportunities and challenges - Elish Kelly; Séamus McGuinness; Anne Devlin (The Economic and Social Research Institute (ESRI), 2024)
Policy evaluation is an essential tool of government as it ensures that the objectives of policies and programmes are being met and that tax revenues are being well spent. In many instances, policy evaluation involves using standard counterfactual analysis to measure the impact of a programme on a well-defined outcome variable, for example, the change in unemployment rates following the introduction of a wage subsidy offered to firms hiring persons on the Live Register. However, in many policy areas with wide-ranging and cross-cutting objectives, standard counterfactual analysis is not possible and policy evaluation takes the form of monitoring changes in key performance indicators (KPIs) that are linked to specific policy objectives or general well-being levels. Given the large-scale budgets associated with rural and community development, it is essential that Ireland's data infrastructure is sufficient to allow for effective policy evaluation in these areas. The purpose of this study is to identify the KPIs most relevant to Irish rural development policy and to assess the extent to which these are currently available at the required spatial level.
Keywords: 330; Entwicklungsplanung; Performance-Messung; Datenqualität; Wirkungsanalyse; Irland